ANALYSIS OF HOUSEHOLD WELF ARE LEVELOF PANDAN WANGI RICE PLANT FARMERSIN TEGALLEGA VILLAGE, WARUNGKONDANG SUBDISTRICT, CIANJUR REGENCY - Yudhanto Dewo G; Endah Djuwendah (Universitas Tribhuwana Tunggadewi, 2020)
The purpose of this research were to 1) Knowing the income of farmer household of Pandan Wangi rice plant in one year period 2) Knowing the expenditure of farmer household of Pandan Wangi rice plant in one year period 3) to analyzing the welfare level of farmer household of Pandan Wangi rice plant. The research uses descriptive qualitative design. The research technique that used is census reasearch technique by interviewing 21 Pandan Wangi Farmers. The result shows that the average income of farmer household of Pandan Wangi rice plant is Rp 41.783.000 per year, and the average per capita income is Rp 10.824.611,4. While the average of expenditure of farmer household of Pandan Wangi rice plant is Rp 30.146.190 per year, with the average of expenditure per capita is Rp 9.362.516. The results of the welfare analysis with 11 indicators levels of welfare 2003 from BPS produces 3 criterias for welfare level of farmer household of Pandan Wangi rice plant, that is high, medium, and low. The welfare level is determined by calculating 11 indicators that have been given different weight. The average of farmer household welfare’s score is 314.76 poins. The result of this analysis is all of the Pandan Wangi farmers have a high level of household welfare.